Interação dos substratos e solução nutritiva no cultivo de orquídea Phalaenopsis em vaso - Rodrigues, Guilherme Feleto (Universidade Federal de São Carlos, 2023)
The flower market in Brazil has been including new technologies that help in the acquisition of higher productivity and more sustainable production systems, including the rational use of water and fertilizers. The main objective of this work was to evaluate the interaction of different types of substrates (fine washed coconut fiber Agrolink®, coal mill, Orquídea Vida Verde® Substrate, polyurethane foam and sphagnum), both without and with the addition of a drainage layer. of gravel at the bottom of the pot, in the potted development of Phalaenopsis orchids. Fertilization was carried out using a nutrient solution based on technical recommendations from a specialized company. The absorption and retention capacity of the nutrient solution by the substrate were also evaluated, as well as monitoring changes in the pH and electrical conductivity of this solution for the different substrates evaluated. A system not conventionally used in cultivation was adopted, in which the nutrient solution is offered next to the water (fertigation) and placed in a plastic container below the cultivation vessel, so that the solution is moved to the substrate due to the difference in water potential between the substrate and the solution. The results showed that treatments with sphagnum substrate and coconut fiber, after being saturated and maintained at a temperature of 20-30°C, in protected cultivation, remained moist for up to 30 days after saturation, while the other substrates remained completely moist. dried in less than 20 days. Regarding the interaction of the nutrient solution with the substrate, it was possible to observe that treatments with Vida Verde® orchid substrate resulted in lower pH averages of the nutrient solution (pH value between 4.0 – 4.5) while charcoal presented higher pH averages (pH = 7.0 - 7.7). The treatments that maintained the cultivation pH within the ideal absorption range were treatments with coconut fiber substrate, sphagnum and polyurethane foam. The treatments with sphagnum and coconut fiber were the treatments with the greatest capacity for retention, absorption and translocation of the nutrient solution through the capillary process. In relation to electrical conductivity, the treatments with the orchid vida verde substrate and coconut fiber were the only ones that had a drop in relation to the EC of the initial solution, with averages below 1.5 ds/cm. The system also presented benefits in relation to water savings compared to traditional irrigation systems, such as micro-sprinkler.
Substrates and nutritive solution in the cultivation of Phalaenopsis orchids under pot culture
Keywords: Orquídeas; Phalaenopsis; Sistema de cultivo; Substratos; Sustentabilidade; Fertirrigação; Orchids; Cultivation system; Plant substrates; Sustainability; Fertigation; CIENCIAS AGRARIAS::AGRONOMIA::FLORICULTURA, PARQUES E JARDINS